Case Report: Successful Implementation of Integrative Cognitive Remediation for Early Psychosis - Vidarsdottir, Olina G.; Roberts, David L.; Twamley, Elizabeth W.; Gudmundsdottir, Berglind; Sigurdsson, Engilbert; Magnusdottir, Brynja B. (Frontiers in Psychiatry, 2021)
Many individuals demonstrate functionally relevant impairment in neurocognition as well as social cognition early on in the course of their psychotic disorder. There is robust evidence supporting cognitive remediation as an effective treatment of cognitive dysfunction in schizophrenia. Increasingly it is accepted that earlier treatment is associated with better outcome and that it is important to systematically assess and treat cognitive dysfunction before the cognitive and functional disabilities are fully realized. However, the clinical availability of these interventions remains sparse. As we move forward with implementing evidence-based interventions into multi-component treatment for early psychosis, it is important to reflect on experience as well as evidence. This case report aims to describe the implementation of an integrative cognitive remediation program in coordinated specialty care (CSC) for early psychosis in Iceland and investigate whether the intervention is sustainable in a CSC setting. Data on the number of patients treated, facilitators trained, groups conducted, and funding was used to assess the sustainability. The results show that since initial implementation in 2016, the intervention has been routinely available as part of standard care, with over 100 patients having received the treatment. The report discusses key factors in the successful implementation of the program.